1986
DOI: 10.1515/bchm3.1986.367.2.905
|View full text |Cite
|
Sign up to set email alerts
|

Fatty-Acid Biosynthesis in Man, a Pathway of Minor Importance. Purification, Optimal Assay Conditions, and Organ Distribution of Fatty-Acid Synthase

Abstract: Fatty-acid synthase has been purified to homogeneity from human liver by a 3-step procedure including protamine sulfate/ammonium sulfate fractionation, affinity chromatography on 2 / ,5'-ADP-Sepharose 4B and gel filtration on Sephacryl S-300. Both the human and rat fatty-acid synthase had similar characteristics regarding molecular mass, subunit structure, amino-acid composition, and substrate affinities. In order to measure the fatty-acid synthase activities in small tissue samples it was necessary to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
21

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 13 publications
2
100
0
21
Order By: Relevance
“…Calculated synthesis rate of palmitate or total non-essential FA based on¯ux through the circulating VLDL-TG pool is`1 ± 2 gad, a small amount compared to the 50 ± 150 g fat in the diet each day. These results con®rm prior conclusions from indirect calorimetry (Tappy et al, 1995; Acheson et al, De novo lipogenesis in humans MK Hellerstein 1982, comparisons of tissue to diet FA composition, and in vitro enzyme measurements (Shrago et al, 1971;Weiss et al, 1986;Sjostrom, 1973) (discussed above). The initial studies were performed in healthy men who were non-obese, non-diabetic, and on high-fat, eucaloric diets in the absence of potential lipogenic stimulators such Figure 1A Schematic model of polymerization biosynthesis.…”
Section: Regulation Of Dnl In Humanssupporting
confidence: 87%
See 2 more Smart Citations
“…Calculated synthesis rate of palmitate or total non-essential FA based on¯ux through the circulating VLDL-TG pool is`1 ± 2 gad, a small amount compared to the 50 ± 150 g fat in the diet each day. These results con®rm prior conclusions from indirect calorimetry (Tappy et al, 1995; Acheson et al, De novo lipogenesis in humans MK Hellerstein 1982, comparisons of tissue to diet FA composition, and in vitro enzyme measurements (Shrago et al, 1971;Weiss et al, 1986;Sjostrom, 1973) (discussed above). The initial studies were performed in healthy men who were non-obese, non-diabetic, and on high-fat, eucaloric diets in the absence of potential lipogenic stimulators such Figure 1A Schematic model of polymerization biosynthesis.…”
Section: Regulation Of Dnl In Humanssupporting
confidence: 87%
“…Most studies (Shrago et al, 1971;Weiss et al, 1986;Sjo Èstrom, 1973;Askanazi et al, 1980) have reported quite low maximal lipogenic rates in human lipogenic tissues compared to rodents, for example (Table 2). These studies might underestimate capacity for inducing DNL, however, since most subjects were studied under typical high-fat eucaloric conditions.…”
Section: Enzyme Activities In Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the levels of FAS in most tissues are low. In human tissue, FAS is distributed in cells involved in lipid metabolism and in hormone-sensitive cells, such as adipocytes, hepatocytes, sebaceous glands, and type II alveolar cells (Weiss et al, 1986). High FAS activity was observed in foetal brain tissue and gradually declined following aging (Salles et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that AMPK activation plays a substantial role in the mechanism, whereby FAS inhibition induces cytotoxicity. As high levels of FAS expression occur commonly in human cancers, but only in a limited number of human tissues, 45 FAS inhibition may selectively activate AMPK in cancer cells whereas sparing most human tissues.…”
Section: Selective Ampk Activationmentioning
confidence: 99%